Penatalaksanaan Holistik pasien Wanita usia 49 Tahun dengan Otitis Eksterna Melalui Pendekatan Kedokteran Keluarga Wilayah Puskesmas Satelit Bandar Lampung. - Putra, Mahardika; Ernawati, Tutik (Medula, 2025)
Otitis externa is an inflammation of the outer ear skin that is commonly caused by excessive ear cleaning, exposure to high humidity, frequent swimming, and prolonged use of earplugs or headsets. The most common pathogens involved in this condition are Pseudomonas aeruginosa and Staphylococcus aureus. Otitis externa is a common condition that can occur in all age groups, although it is rarely found in children under two years of age. Its incidence peaks between the ages of 7 and 14, with approximately 10% of the population experiencing the condition at some point in their lives, and 95% of cases being acute. There is no difference in incidence based on gender. Studies in the Netherlands and the United Kingdom report an annual incidence of approximately 1%, while data from the Centers for Disease Control and Prevention (CDC) indicate approximately 2.4 million visits per year due to acute otitis externa in the United States (8.1 visits per 1,000 population). In developing countries, the prevalence is reported to reach 17.5%. This report is a case study conducted using a family medicine approach, involving the identification of risk factors, clinical issues, and evidence-based medicine management with a family-oriented, patient-centered, and community-based approach. Primary data was obtained through self-reporting, physical examination, and home visits, while secondary data was derived from patient medical records. The evaluation was conducted holistically through qualitative and quantitative approaches from the beginning to the end of the study.